El Excentrico, 1959-04-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
April 20, 1959 [5 de abril de 1959]. Ano 9, No. 16. Cover contains a photo of Aurie Gutierrez kissing Bonie Villegas on the cheek after he was awarded a trophy. The headline reads, "Bonie Villegas awarded trophy, receives kiss from Aurie Gutierrez."